Humanising the university to progress towards a more inclusive model. An approach from social pedagogy - María Naranjo Crespo (Revista Española de Pedagogía, 2025)
Research in social pedagogy is situated within a methodological framework that must be consistent with the epistemological principles of the discipline. These include the premises from the classic approaches of critical pedagogies, as well as other more contemporary models that allow these postulates to be specified within the framework of current neoliberalism, such as post-feminist, inclusive, decolonial or common good pedagogies, among others. Taking these positions into account, we present a case study whose objective has been to analyse the elements that define the processes of inclusion of socioeconomically and culturally disadvantaged students in a university institution. The research is qualitative in nature and includes elements from ethnographic study designs. Forty-seven people from different groups in the university community took part in the study, using the in-depth interview as the central data production technique, as well as the field diary and a review of institutional documentation. Data analysis was carried out by coordinating a system of open, axial and selective coding. The final results obtained from the selective coding are defined in relation to seven themes: (1) otherness as the basis of discrimination and exclusion; (2) the positive and the threatening; (3) envisioning utopia and acting on reality; (4) university education as a liberating or banking praxis; (5) the university must be constituted as an inclusive space: from the adaptation of individuals to the transformation of the environment; (6) on groups and identities: labels, stigmatisation and visibilisation; (7) the representation of reality from the voices of the participants. The final considerations address two paradigms that define the institutional culture that underlies the definition of inclusive models: the claims of humanising the university or the university for excellence and the elite.